‘No Polycarps among Us’? Questions for Reformed Political Theology Today - Smit, Dirk J. (Studies in Christian ethics, 2015)
Offering an overview of challenges and questions, the essay situates contemporary directions and developments in Reformed thought about political ethics by considering whether four well-known slogans from the tradition of Reformed political thought are still meaningful and credible under changed conditions today. The four slogans, integrally related to one another, are the lordship of Christ, the prophetic role of the church, the love for justice, and the importance of calling. The essay draws primarily on recent South African experiences, where the Reformed tradition was deeply involved in both apartheid theology and the church struggle against apartheid. It engages with the North American Reformed philosopher Nicholas Wolterstorff as main interlocutor, since his own interest in political theology and his own convictions about justice and rights also developed in direct engagement with his own South African experiences.